Big Brother ‘Titans’ Show and Cable Subscription: A Case Study of GOTV Subscribers in Uyo - Udoudom, Uduak Imoh; Pam, Christiana Chundung; Igiri, Anthony Bassey (Darul Yasin Al Sys, 2023)
This study explored the impact of the popular reality TV show, Big Brother 'Titans', on cable subscriptions among GOTV subscribers in Uyo. A survey questionnaire was distributed among a representative sample of 322 GOTV subscribers in Uyo, focusing on their viewership habits, motivations for subscribing to GOTV, and the influence of Big Brother 'Titans' on their subscription decisions. The findings revealed that Big Brother 'Titans' has a significant impact on the cable subscription patterns of GOTV subscribers in Uyo. The majority of respondents reported watching the show regularly and acknowledged that it was a primary reason for their subscription. The captivating nature of the show, coupled with its interactive elements and the sense of community it fostered, emerged as key motivators for maintaining their GOTV subscriptions. The study concluded that